Four New Species and Additional Distributions of Elaphoglossum Section Elaphoglossum (Dryopteridaceae) from the Neotropics - Rojas Alvarado, Alexander (2017)
Four new species of Elaphoglossum sect. Elaphoglossum are described: E. amparoanum A. Rojas, E. chocoense A. Rojas, E. fayorum A. Rojas and E. luciae A. Rojas. The first species is related to E. variolatum Mickel, but differs from it by having rhizome scales bicolorous and long ciliate margin. The second species is different to E. moranii Mickel by having narrower rhizome, shorter stipe, elliptic blade, attenuate blade base, shorter fertile fronds with blackish costa and present at lower altitudinal distribution. After that, the third species differs from E. lingua (C. Presl) Brack. by pale rhizome scales with long ciliate margin, shorter fronds and blade scales denser and lighter. Finally, the fourth species is related to E. atrosquamatum Mickel, but with relative longer fronds and broader blade. The geographical distributions of E. guatemalense (Klotzsch) T. Moore, E. longicrure Christ, E. minutum (Pohl ex Fée) T. Moore and E. nicaragüense A. Rojas are expanded.